Coretax Literacy and Regulatory Agility in Taxpayer Compliance Assistance: The Mediating Role of Digital Advisory Capability - Melvin Rahma Sayuga Subroto; Zulfatun Ruscitasari; Andreas Kuncoro (Academic Bright Collaboration, 2026)
Purpose – This study examines how Coretax Literacy and Regulatory Agility influence the Effectiveness of Taxpayer Compliance Assistance through Digital Advisory Capability among tax consultants in the Special Region of Yogyakarta. The study responds to the limited explanation of tax consultants as professional intermediaries during the Coretax transition. Methods – This research used an explanatory quantitative survey design. Data were collected from 100 tax consultants and tax practitioners in the Special Region of Yogyakarta using purposive sampling. The model was tested using partial least squares structural equation modeling (PLS-SEM). Sample adequacy was confirmed using G*Power, while predictive relevance was assessed using PLSpredict. Findings – Coretax Literacy significantly affected Digital Advisory Capability (β = 0.372, p < 0.001), but did not directly affect assistance effectiveness (β = 0.077, p = 0.207). Regulatory Agility significantly affected Digital Advisory Capability (β = 0.538, p < 0.001) and assistance effectiveness (β = 0.373, p < 0.001). Digital Advisory Capability significantly affected assistance effectiveness (β = 0.534, p < 0.001). It fully mediated the effect of Coretax Literacy (β = 0.198, p < 0.001) and partially mediated the effect of Regulatory Agility (β = 0.287, p < 0.001). The model explained 80.1% of the variance in assistance effectiveness and showed positive predictive relevance (Q²predict = 0.679). Research implications – The findings imply that Coretax training for tax consultants should emphasize not only system literacy but also advisory translation, regulatory interpretation, and digital problem-solving capability. However, the single-source self-report design and high proximity between advisory capability and assistance effectiveness require cautious interpretation. Originality – This study shifts Coretax research from taxpayer-focused analysis to tax consultants as digital compliance intermediaries, integrating the dynamic capabilities perspective and the digital advisory framework to explain how system literacy and regulatory agility are converted into compliance outcomes.